2011
DOI: 10.1007/s12550-011-0087-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of different storage conditions on the mycotoxin contamination of Fusarium culmorum-infected and non-infected wheat straw

Abstract: Mycotoxins are known to affect the health and performance of farm animals. In contrast to cereal grains, the straw is only rarely analysed for mycotoxins, although contaminated straw could additionally expose farm animals to mycotoxins. For this reason, two experiments were carried out to examine the effect of pre-harvest Fusarium infection (inoculation with F. culmorum) and different storage conditions on the mycotoxin concentrations in straw. In the first experiment, both the inoculated and the identically c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Moreover, the diversity of the fungal population differed according to the egg-laying hen housing system. The fungal species present on the eggshell surface may occur in the environment of the henhouse [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the diversity of the fungal population differed according to the egg-laying hen housing system. The fungal species present on the eggshell surface may occur in the environment of the henhouse [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the deep litter indoor housing system, the contamination is usually caused by moist litter or dirty nests. Researchers studying different types of litter found that it contained fungi from Aspergillus , Cladosporium , Drechslera , Penicillium , Stemphylium and Fusarium genera [ 9 , 10 , 11 ]. Straw chaff was found to be the most contaminated as its CFU/g was the highest (28.49 log CFU/g).…”
Section: Introductionmentioning
confidence: 99%
“…Yield and quality losses are particularly important when F. culmorum induces FHB, which develops from infection at anthesis and spreads until grain harvest, causing grain contamination with mycotoxins, such as type B trichothecenes, zearalenone and fusarins (Hope et al, 2005;Jennings et al, 2004;Kammoun et al, 2010;Lacey et al, 1999;Placinta et al, 1999;Rohweder et al, 2011;Visconti and Pascale, 2010). The sesquiterpene epoxide trichothecenes are considered to be the most bioactive compounds produced by F. culmorum.…”
Section: Introductionmentioning
confidence: 99%
“…Because the sampling was carried out only a few days after harvest, except for the stored oat straw, it suggests that the measured straw concentrations of mycotoxins were most likely present at the time of harvest. In experimental studies, Rohweder et al ( 2011 ) observed decreased DON levels and increased ZEN levels when inoculated straw was stored outdoors for longer periods. No kernel contamination in the collected straw samples was observed.…”
Section: Discussionmentioning
confidence: 99%